Human papillomavirus infection among male adolescents and young adults with perinatally-acquired HIV and without HIV in Thailand. (September 2019) - Wittawatmongkol, Orasri; Gatechompol, Sivaporn; Kerr, Stephen J; Chalermchockcharoenkit, Amphan; Teeratakulpisarn, Nipat; Lermankul, Watcharee; Thamkhantho, Manopchai; Phanuphak, Nittaya; Sohn, Annette H; Chokephaibulkit, Kulkanya; ,
HIV infection may increase the risk of persistent human papillomavirus (HPV) infection and complications. Male adolescents and young adults (AYAs) with perinatally-acquired HIV (PHIV) and without HIV in Thailand were matched by age and lifetime number of sexual partners. HPV infection at oral, anal, penile, and scrotal sites was detected by polymerase chain reaction. A total of 49 PHIV and 47 HIV-uninfected male AYAs (median age 18 [17–20] years) were enrolled (June 2013–September 2014). Overall, 18 were men who have sex with men (MSM) (12% of PHIV, 26% of HIV-uninfected AYAs; P  = 0.12). Among the PHIV, the median (interquartile range) CD4 cell count was 573 (434–747) cells/mm 3 and 69% had HIV RNA <40 copies/ml. The prevalence of any HPV infection was 61% in PHIV and 49% in HIV-uninfected AYAs ( P  = 0.23) and that of high-risk HPV was 33% in PHIV and 28% in HIV-uninfected AYAs ( P  = 0.59). Among those with HPV, 55% had any high-risk HPV type and 28% had HPV-16 and/or HPV-18. In multivariate models, smoking (OR 6.10, 95% CI, 1.19–31.35, P  = 0.01) and prior history of STI symptoms (OR 5.01, 95% CI, 1.63–15.40, P  = 0.004) were associated with high-risk HPV infection. HPV vaccination in early adolescence presents a valuable but missed prevention opportunity.